Pengaruh Lingkungan Kerja Motivasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai Badan Perencanaan Pembangunan Daerah Kabupaten Tapanuli Tengah - Despi Erwanto; Beni Supriadi Sarumaha; Indra Permana; Very Wealthy Saragih (Universitas Islam Sumatera Utara, 2022)
This formula research internal issue is how influence of work environment on employees performance. How influence of motivation on employees performance. How influence of leadership style on employees performance. How influence of work environment, motivation, and leadership style on employees performance. This research target is to for know influence and analyze work environment on employees performance. For know influence and analyze motivation on employees performance. For know influence and analyze leadership style on employees performance. For know influence and analyze work environment, motivation, and leadership style on employees performance. Sample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of work environment effect positive and significant on employees performance. Motivation effect positive and significant on employees performance. Leadership style effect positive and significant on employees performance. Work environment, motivation and leadership style effect and positive and significant on employees performance